Competition and Risk Taking in Local Bank Markets: Evidence from the Business Loans Segment - Chiara Canta; Øivind A. Nilsen; Simen A. Ulsaker; Øivind Anti Nilsen (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper studies empirically the relationship between competition and risk taking in banking markets. We exploit an unique dataset providing information about all bank loans to Norwegian firms over several years. Rather than relying on observed market shares, we use the distance between bank branches and firms to measure the competitiveness of local markets. The cross-sectional and longitudinal variation in competition in local markets are used to identify the relationship between competition and risk taking, which we measure by the non-performing loans and loss provision rates of the individual banks. We find that more competition leads to more risk taking. We also examine the effects of bank competition on the availability of loans. More competition leads to lower interest rates and higher loan volumes, but also makes it more difficult for small and newly established firms to obtain a loan.
Keywords: G21; L11; L13; 330; banking; local competition; risk taking; firm behaviour